2014
DOI: 10.1007/s40618-014-0106-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-functioning adrenal incidentalomas are associated with higher hypertension prevalence and higher risk of atherosclerosis

Abstract: There is increasing evidence that several cardiometabolic risk factors occur with higher prevalence in non-functioning adrenal incidentaloma patients compared to age-matched healthy subjects. In our study, hypertension prevalence and CIMT were higher in the NFAI group. Serum adipokine levels were similar for both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 17 publications
5
31
0
1
Order By: Relevance
“…However, emerging evidence suggests that even apparent NFAT have a higher cross-sectional association with cardiometabolic derangements, such as insulin resistance, when compared with matched controls without adrenal tumors (1719), possibly because NFAT secrete low-levels of glucocorticoids (17, 20). Although the size of these aforementioned studies was small and lacked longitudinal follow-up, collectively they suggest that NFAT, defined by our current clinical practice guidelines (1, 2, 15, 16, 21), may not be “non-functional” after all; they may impart cardiometabolic risk by secreting inappropriate amounts of adrenal hormones that evade our traditional clinical criteria and detection capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…However, emerging evidence suggests that even apparent NFAT have a higher cross-sectional association with cardiometabolic derangements, such as insulin resistance, when compared with matched controls without adrenal tumors (1719), possibly because NFAT secrete low-levels of glucocorticoids (17, 20). Although the size of these aforementioned studies was small and lacked longitudinal follow-up, collectively they suggest that NFAT, defined by our current clinical practice guidelines (1, 2, 15, 16, 21), may not be “non-functional” after all; they may impart cardiometabolic risk by secreting inappropriate amounts of adrenal hormones that evade our traditional clinical criteria and detection capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the findings of recent studies, patients with AI have increased cardiovascular risk (3, 7). Patients with AI have increased prevalence of metabolic syndrome and impaired endothelial function (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AI have increased prevalence of metabolic syndrome and impaired endothelial function (9, 10). Patients with incidentalomas have higher hypertension prevalence and higher risk of atherosclerosis measured as increased CIMT (3). Iacobellis et al showed early LV structural changes in asymptomatic non-functioning AI, such as increased left ventricular mass (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations